Estudo sobre o panorama da energia elétrica no Brasil e tendências futuras - Morais, Luciano Cardoso de [UNESP] (2015)
The main goal of this work is to study and to map the electrical energy scenario in Brazil, considering the supply, demand and the different primary energy sources in the country. It is well skown that almost 70% of the electrical energy consumed in Brasil comes from hydroelectric plants, however, since 2013 and due to the lack of abundant rain for keeping the hydroelectric normal parameters, it has become necessary to apply thermoelectric plants, consequently increasing the energy costs. For this reason, different energy sources are studied in this work as alternatives for the current generation system in Brazil, considering the different aspects such as: installation costs, normative and financial incentives and future demand. Furthermore, to better understand the potential of renewable energy in Brazil, some comparisons using the German and Chinese scenarios have been done, allowing to suggest short and long term actions for increasing the sustainable energy market, pointing out solar and wind power sources as essential for the economic and environmental development